Tuning PID Controller Using Multiobjective Ant Colony Optimization. (17th April 2012) - Chiha, Ibtissem; Liouane, Noureddine; Borne, Pierre
Abstract : This paper treats a tuning of PID controllers method using multiobjective ant colony optimization. The design objective was to apply the ant colony algorithm in the aim of tuning the optimum solution of the PID controllers (K p, K i, and K d ) by minimizing the multiobjective function. The potential of using multiobjective ant algorithms is to identify the Pareto optimal solution. The other methods are applied to make comparisons between a classic approach based on the "Ziegler-Nichols" method and a metaheuristic approach based on the genetic algorithms. Simulation results demonstrate that the new tuning method using multiobjective ant colony optimization has a better control system performance compared with the classic approach and the genetic algorithms.